Psychological testing and assessment : an introduction to tests and measurement - Cohen, Ronald Jay; Swerdlik, Mark E.; Sturman, Edward (New York, NY : McGraw-Hill education, 2013)
Psychological Testing and Assessment presents students with a solid grounding in psychometrics and the world of testing and assessment. The book distinguishes itself through its logical organization, readable text, and many pedagogical aids, such as the "Meet an Assessment Professional" feature in every chapter which highlights the works of people such as Dr. Stephen Finn, architect of therapeutic assessment. Now in its eighth edition, this text has consistently won enthusiastic reviews not only for its balance of breadth and depth of coverage, but for content that brings a human face to the assessment enterprise. -- publisher
Keywords: Psychological tests